(untitled) (Per Musi, 2021)
This paper addresses aspects related to the singer’s creation processes and brings also their dialogue with the composers’ creation work, which includes the issues of Umwelten (Vieira 2008, 2009), the Peircean concepts of subject and self (Colapietro 1989, 2003), the concept of miscegenation (Laplantine and Nouss 2002), supports (written or oralized), and ecological perception, as conceptualized by J. Gibson (1979). In order to contribute to the reflection on these aspects, some testimonies from singers about their interpretative creations of the Canção de Amor [Song of Love], by Villa-Lobos, were brought. The objective is to expose the details of their creative processes, otherwise inaccessible to the public. These testimonies are part of our doctoral thesis defended in the line of research of Creative Processes. We also refer to resources from the processes criticism and nets of creation by Cecilia Salles (2006, 2008, 2010, 2011).